ANALYSIS OF WHETHER CIVIL PROCEDURE RULES OF COURT ARE SUPERIOR TO THE LAW ESTABLISHING SUCH COURT: A CASE FOR THE REVIEW OF TARABA STATE AREA COURTS EDICT 1988 AND THE AREA COURTS (CIVIL PROCEDURE) RULES 1971 - Okeokwo, ThankGod; Linus, Gadzama, Christopher (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
Civil Procedure Rules are made out of the powers conferred on the enacting Judicial Officer usually the Chief of the State to make practice and procedure for administration of justice in Courts within such state. It is an exercise of powers derived from the principal law. The principal law is the foundation while the procedure or practice is built on the foundation. The principal law is superior and should have overriding effect over the procedural law if both comes in conflict on an issue regarding administration of justice and procedure in Courts. This article aim to query and ascertain the propriety or otherwise of civil procedure rules of a court being interpreted to be superior to the law which established such court or interpreted to mean that until powers of the Chief Judge to make recent civil procedure is activated, the literal meaning of the words of the establishing law will not be superior to extant civil procedure rules. The article adopts the doctrinal methodology with particular reliance on sections of the Taraba State Area Courts Edict 1988 and the Area Courts (Civil Procedure) Rules 1971. It consulted secondary sources related to the topic. The article found that the Taraba State Area Courts Edict 1988 and the Area Courts (Civil Procedure) Rules 1971 predates the creation of Taraba State and do not represent a 21st century legal framework for administration of justice in the state. It recommended that the Taraba State House of Assembly amend the Area Courts Law while the Chief Judge should urgently issue a new Area Courts (Civil Procedure) Rules for the State.